Antireflective “moth-eye” structures on tunable optical silicone membranes - Brunner, Robert; Spatz, Joachim P. (Applied optics, 2012)
Flexible silicone membranes are key components for tunable optical lenses. The elastic operation of the membranes impedes the use of classical layer systems for an antireflective (AR) effect. To overcome this limitation, we equipped optical elastomer membranes with “moth-eye” structures directly in the flexible silicone substrate. The manufacturing of the AR structures in the flexible membrane includes a mastering process based on block copolymer micelle nanolithography followed by a replication method. We investigate the performance of the resulting AR structures under strain of up to 20% membrane expansion. A significant transmittance enhancement of up to 2.5% is achieved over the entire visible spectrum, which means that more than half of the surface reflection losses are compensated by the AR structures.